Pension Asset Allocation in the UK: a Quantitative Study. - Shi, Binbin (2007)
In recent years, pension crisis has drawn large public attentions. The investment strategy behind the pension funds has also been of a concern. The long popularized pension investment inertia: the cult of the equity lies in the centre of the debate. In a changing practice: the poor stock market returns, the rising costs of pensions, the strict prescription imposed by accounting and regulatory forces, the increasing cash outflows, all these factors challenge the cult of the equity. Due to the pension crisis, institutional investors are more aware of investment risk. Investment strategy has a tendency to shift from risk-seeking or profit-seeking to liability matching strategy. This paper summarizes the background information in terms of pension funds and briefly discusses the current position of UK pension funds and the history of UK pension scheme asset allocation, followed by a detailed discussion of the general principles for asset allocation. The data used is from the annual reports of the FTSE100 companies at 1st January 2006. The statistical results show that asset allocation of a pension scheme is influenced by the scheme's financial strength. The later year's asset allocation depends on former year's asset allocation. Factors such as pension scheme size, expected equity risk premium, and actuarial advice are not determinants of asset allocation.